The dual nature of neuroinflammation in networked brain - Ludmila Müller; Svetlana Di Benedetto; Viktor Müller (Frontiers in Immunology)
Neuroinflammation is a dynamic, context-sensitive process that plays essential roles in brain development, maintenance, and response to injury. It reflects a finely balanced neuroimmune state—facilitating repair and adaptation under homeostatic conditions, while also contributing to dysfunction when dysregulated or chronically activated. In this mini-review, we examine the cellular and molecular mechanisms underlying neuroinflammatory responses, focusing on the roles of microglia and astrocytes, their bidirectional communication with neurons, and their interaction with peripheral immune signals. We describe how various stimuli—including aging, protein aggregates, and cellular stress—modulate glial function and shift immune activity toward protective or deleterious outcomes. Special attention is given to endogenous regulatory pathways, including cytokine signaling, receptor-mediated crosstalk, and immunometabolic cues that determine the resolution or persistence of inflammation. We further discuss shared and disease-specific features of neuroinflammation across neurological disorders, offering a systems-level perspective on how immune activity contributes to neural resilience or degeneration. This integrated view aims to inform future studies on neuroimmune dynamics in health and disease.